The global response to HIV/AIDS in sub-Saharan Africa: achievements, challenges, and perspectives for the future - Orlando, Stefano; Silaghi, Loredana Andreea; Cicala, Mariagrazia; Lowole, Mathambo William; Massango, Cacilda; Lunghi, Roberto; Mamary, Hawa Sangarè; Ciccacci, Fausto; Scarcella, Paola (Frontiers in Public Health, 2025)
Over four decades, the global response to HIV/AIDS has transformed the disease into a manageable chronic condition, driven by advances in antiretroviral therapy, global financing, and ambitious targets like the 90-90-90 and 95-95-95 goals. Yet HIV remains a major challenge, especially in sub-Saharan Africa, which bears the highest burden worldwide. While AIDS-related mortality has declined, the number of people living with HIV continues to grow, placing significant strain on health systems and financial resources. Persistent challenges include high rates of new infections, late diagnoses, inequalities in access to care, and barriers faced by key populations. Emerging issues such as drug resistance and declining political commitment risk reversing progress. Investments in HIV have yielded broader benefits for health systems, supporting integration with services for tuberculosis and noncommunicable diseases. This review traces the global HIV response, analyses current epidemiological and economic trends, and highlights strategic priorities to sustain progress. Key strategic directions include reducing costs and expanding access to advanced diagnostics and antiretroviral therapy; prioritizing comprehensive, high-quality care over simplified delivery models that risk compromising diagnostic accuracy and fostering drug resistance; integrating HIV programs with services for other diseases, including noncommunicable diseases; strengthening surveillance and management of HIV drug resistance; and sustaining the visibility of HIV while addressing the needs of marginalized populations.